2003
DOI: 10.4049/jimmunol.170.3.1481
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P4502D6193–212: A New Immunodominant Epitope and Target of Virus/Self Cross-Reactivity in Liver Kidney Microsomal Autoantibody Type 1-Positive Liver Disease

Abstract: Cytochrome P4502D6 (CYP2D6), target of liver kidney microsomal autoantibody type 1 (LKM1), characterizes autoimmune hepatitis type 2 (AIH2) but is also found in patients with chronic hepatitis C virus (HCV) infection. To provide a complete linear epitope B cell map of CYP2D6, we tested peptides spanning the entire sequence of CYP2D6. In addition to confirming previously described antigenic sites, we identified four new epitopes (193–212, 238–257, 268–287, and 478–497). CYP2D6193–212 is immunodominant and was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(153 citation statements)
references
References 29 publications
2
144
0
7
Order By: Relevance
“…Furthermore, it has been shown that some of these epitopes share structural homologies with protein sequences present in type 1 herpes simplex virus and hepatitis C virus (17,21). The use of deleted CYP mutants has also provided important information concerning the structure of different epitopes present in CYP2C9, CYP3A1, and CYP1A2 (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been shown that some of these epitopes share structural homologies with protein sequences present in type 1 herpes simplex virus and hepatitis C virus (17,21). The use of deleted CYP mutants has also provided important information concerning the structure of different epitopes present in CYP2C9, CYP3A1, and CYP1A2 (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…We focused our attention to protruding areas suitable for antibody binding, whereas sequences that were in troughs or not apparently accessible were excluded. Since most of the epitopes so far identified in CYPs largely involve the C-terminal portion of the molecule (15)(16)(17)(18)(19)(20)(21), the sequence between amino acids 200 and 493 was investigated. Preliminary experiments using purified rat or rabbit CYP2E1 showed that human anti-CYP2E1 IgG cross-reacted with the enzyme from these species in enzyme-linked immunosorbent assays (not shown).…”
Section: Cyp2e1 Conformational Epitopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction for a given peptide was considered positive when optical density (OD) test /OD control peptide was 2 or more, this cutoff representing the mean ϩ 5 SD of 135 readings using serum (tested in triplicate) from 15 healthy subjects against the mimicking peptides. 5,15,22,26,28 Inhibition Studies. To investigate whether the simultaneous reactivity to LACDE BGAL 266-280 and human PDC-E2 212-226 was due to cross-reactivity, competition ELISAs were performed, measuring residual IgG3 anti-LACDE BGAL 266-280 or anti-PDC-E2 212-226 reactivity after preincubation respectively with LACDE BGAL 266-280 , PDC-E2 212-226 , purified PDC antigen, control peptide, and control antigen (CYP2D6, Pharmacia & Upjohn) as liquid phase competitors, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether the simultaneous reactivity to LACDE BGAL 266-280 and human PDC-E2 212-226 was due to cross-reactivity, competition ELISAs were performed, measuring residual IgG3 anti-LACDE BGAL 266-280 or anti-PDC-E2 212-226 reactivity after preincubation respectively with LACDE BGAL 266-280 , PDC-E2 212-226 , purified PDC antigen, control peptide, and control antigen (CYP2D6, Pharmacia & Upjohn) as liquid phase competitors, as previously described. 5,15,22,26,28,29 Inhibition of anti-ECOLI PDC-E2 231-245 reactivity was measured under conditions similar to those described for LACDE BGAL [266][267][268][269][270][271][272][273][274][275][276][277][278][279][280] .…”
Section: Methodsmentioning
confidence: 99%